2017
DOI: 10.5152/eej.2017.17024
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of the Prevalence of Pulp Stones in a Yemeni Population Sample

Abstract: To determine the prevalence and distribution of pulp stones in the posterior teeth of a sample of adult Yemeni dental patients using digital panoramic radiographs. Methods: In total, 913 panoramic radiographs from patients attending the hospital dental clinics of at University of Sciences and Technology, Sana'a, Yemen, from January 2013 to December 2014 were examined. The occurrence of pulp stones in the posterior teeth of adult subjects was recorded. Associations between pulp stones and gender, age, arch, sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
(87 reference statements)
8
11
1
Order By: Relevance
“…This finding is in agreement with other studies previously reported by (Bains et al, 2014;Colak et al, 2012;Kannan et al, 2015;Ravanshad et al, 2015;Sisman et al, 2012;Tamse et al, 1982;Turkal et al, 2013). However, some studies have shown that pulp stones were more prevalent in males than in females, and other studies have reported no significant differences between genders (Al-Nazhan and Al-Shammrani, 1991;Baghdady et al, 1988;Kalaji et al, 2017;Ranjitkar et al, 2002). A possible explanation for this difference may be attributed to the bruxism which is more prevalent in females.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with other studies previously reported by (Bains et al, 2014;Colak et al, 2012;Kannan et al, 2015;Ravanshad et al, 2015;Sisman et al, 2012;Tamse et al, 1982;Turkal et al, 2013). However, some studies have shown that pulp stones were more prevalent in males than in females, and other studies have reported no significant differences between genders (Al-Nazhan and Al-Shammrani, 1991;Baghdady et al, 1988;Kalaji et al, 2017;Ranjitkar et al, 2002). A possible explanation for this difference may be attributed to the bruxism which is more prevalent in females.…”
Section: Discussionsupporting
confidence: 92%
“…The result of this study on a group of Libyan dental patients has shown an overall prevalence of 30.2% for individuals and 8.4% for all examined teeth. This prevalence was higher than the results of previous studies by (Gulsahi et al, 2009) 5% and by (Turkal et al, 2013) 2.1% in Turkish population, (Kalaji et al, 2017) (Baghdady et al, 1988) 14.8% in Iraqi population, (Al-Nazhan and Al-Shammrani , 1991) 10.2% in Saudi population, (Kannan et al,2015) 15.7% in Malaysian population, (Bains et al,2014) 9.09% in Indian population, and (Ravanshad et al,2015) 11.25% in Iranians population. These differences in prevalence in different populations and different geographic areas may be attributed to the variation of conditions related to the studied population, such as ethnicity, dental care, and dental habits.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…On comparing with the previous literature, several studies observed similar results, where Sandeepa et al 15 and Panwar et al 21 found that pulp stones were most commonly found in the maxillary first molars than mandibular first molars. Kalaji et al 25 also observed in their study that the occurrence of pulp stones is evidently higher in the maxilla than the mandible for each tooth type. According to Yousuf and Antony, 23 maxillary arch is the most affected arch, and also the pulp stones were higher in the maxillary first molar teeth.…”
Section: Discussionmentioning
confidence: 71%
“…Most studies reported that the frequencies of pulp stones were highest in molars [12,[20][21][22][23][24]. Given the fact that pulp stones smaller than 200 µm are not shown in radiographs, it is possible that the prevalence of pulp stones is estimated lower than the real amount [7].…”
Section: Copyright © Helen Rushdi Ayoubimentioning
confidence: 99%